Thixotropy of reactive suspensions: application to white portland cement suspensions. - Ojeda Farías, Omar Farid (2019)
Portland cement pastes are concentrated suspensions consisting of two interacting phases: solid and reactive with the binder and liquid with the water and its admixtures. The solid particles are composed of calcium silicate and aluminate phases, which once dispersed in water lead to strong ionic dissolution, saturation and precipitation of surface layers, followed by a period of low reactivity called dormant period. During this period hydrate products nucleate and grow to form portlandite, ettringite and CSH gel followed by a faster hydration process known as acceleration period. In the dormant period the consistency is workable until the ions precipitation starts the suspension setting.